Aligning quality improvement with better child health for the 21st century. Issue 6 (18th December 2020) - Singh, Guddi; Cribb, Alan
Abstract : Quality improvement (QI) has tremendous potential to tackle the shortcomings of health services. But health professionals have not yet fully embraced QI as part of their day-to-day concerns. Indeed, QI is sometimes experienced as a brake on quality rather than a catalyst for improvement. This can happen, for example, if there is too much emphasis on meeting short-term institutional goals rather than on addressing long-term health needs. This emphasis also risks equating quality with safety and efficiency measures while neglecting patient-centredness and equity. QI does not have to be like this. We suggest that the conscientious and critical engagement of health professionals in QI can lead to genuinely better and more far-reaching outcomes for child health. We also distinguish between QI projects that repair the status quo and those that seek to reform it, arguing that there is an important place for both.